2020
DOI: 10.3390/dj8030078
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Treatment of Peri-Implantitis: Case Series

Abstract: Peri-implantitis is one of the most important biological complication of dental implants. It has inflammatory nature, proved association with plaque accumulation in peri-implant tissues, and can be progressive on background of several factors, like comorbidity factors and bad habits. The prophylaxis and different methods of treatment were discussed during last 30 years, and surgical and nonsurgical techniques have their foes, benefits, and disadvantages. In this article, we describe the case series of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…Mensi et al reported improvements in PPD and BOP using a Multiple Anti-Infective Non-Surgical Treatment (MAINST) protocol that consisted of two treatments, each executed in two consecutive weeks, based on air polishing, ultrasonic, manual debridement, chlorhexidine rinse, and a final pocket filling with doxycycline gel 14% (Ligosan ® Kulzer Gmbh, Hanau, Germany) [ 56 ]. The same results were also reported in Moura et al and Diachova et al, where improvements in PD [ 57 , 58 ] and BOP [ 58 ] were registered after using local doxycycline. These findings confirmed Butcher et al (2004), who demonstrated a significant improvement in peri-implant disease after applying doxycycline as a local antibiotic [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…Mensi et al reported improvements in PPD and BOP using a Multiple Anti-Infective Non-Surgical Treatment (MAINST) protocol that consisted of two treatments, each executed in two consecutive weeks, based on air polishing, ultrasonic, manual debridement, chlorhexidine rinse, and a final pocket filling with doxycycline gel 14% (Ligosan ® Kulzer Gmbh, Hanau, Germany) [ 56 ]. The same results were also reported in Moura et al and Diachova et al, where improvements in PD [ 57 , 58 ] and BOP [ 58 ] were registered after using local doxycycline. These findings confirmed Butcher et al (2004), who demonstrated a significant improvement in peri-implant disease after applying doxycycline as a local antibiotic [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…The results of the study demonstrated the safety of such early disposal of the stent, which corresponds to the results of the works of other authors. In two comparative studies, the authors demonstrated the safety and effectiveness of stent removal one week after surgery [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Применение данных материалов способствует увеличению скорости процессов регенерации и минерализации костной ткани. Среди них препараты на основе гидроксиапатита и коллагена наиболее предсказуемы, эффективны и отличаются широким диапазоном возможного применения для устранения дефектов челюстей различной этиологии [9][10][11][12] .…”
Section: Introductionunclassified